Student perception towards higher education service quality: a case study at research and non-research universities in Malaysia - Rahida Abd Rahman; Azleen binti Ilias (IDEAS, 2024)
In determining the service quality in public and private universities or Higher Education Institutions (HEIs), customer satisfaction (for service-oriented organizations) or, in this case of quantitative research, students’ satisfaction evaluation and assessment is very significant. Universities constantly gain, sustain, and develop deeper relationships with their students to stay competitive. The purpose of this research paper is, first and foremost, to examine the relationship between Parasuraman’s SERVQUAL model service quality dimensions (which are tangibility, reliability, responsiveness, assurance, and empathy) and students’ satisfaction. Secondly, this study aims to identify critical factors in Parasuraman’s SERVQUAL model service quality dimensions (tangibility, reliability, responsiveness, assurance, and empathy) that contribute the most towards students’ satisfaction. This study used a set of questionnaires (online survey) for 200 respondents (students pursuing bachelor’s degrees) from two public universities in Selangor, randomly chosen from the list of public universities available in Selangor. The two public universities are Universiti Kebangsaan Malaysia (UKM as a research university) and Universiti Islam Antarabangsa Malaysia (UIAM as a non-research university). A simple random sampling is used in this research. This empirical finding analyzed by correlation and multiple regression provides evidence for Parasuraman’s SERVQUAL model in an academic context, which was related to the factors that contribute towards students’ satisfaction, thus attracting more students to the respective university or higher education institutions in the future.